- Fiqh differences in Fighting Albaghi’s People Book from Ibn- Qudama’s Book Almughni - A Comparative Study in Fiqh - alnujaim, Hessah Nasser (Journal of Islamic Sciences, 2020)
This study contains a collection of Fiqh differences which is written in IbnQudama’s book "AlMughni" in total three differences. The goals of this search are: First, gathering all Fiqh differences related to the study. Second, illustrating aspects of agreement and differences between similar issues. Third, describing the methodology applied by Ibn Qudama’s book in explaining Fiqh differences through study issues. This study based on the application of the inductive comparative analytical approach. The results of the study are the following: • the significant in terms of the usefulness of Fiqh science to lead the Muslims to right judments to build a more stable and secure society. 2.Ibn Qudama distinguished with his sharp intelligent because all the differences in his book which were three were strong differences.